Copper (I) complexes of 2-thiouracil - (:unkn) unknown (NATL INST SCIENCE COMMUNICATION, 2007)
Copper complexes obtained from the reactions between 2-thiouracil and cupric hydroxide in different solvents have been investigated. Mononuclear or polynuclear complexes of Cu(I) have been obtained depending on the reaction conditions. Hydroxo complexes of copper(I) have been obtained at pH around 3.5. 2-Thiouracil acts as mono- or bidentate ligand in complexes. [Cu(H2TU)2 OH], [Cu-5(H2TU)(6) (OH)(5)] and [Cu-3(H2TU)(4)(HTU)(OH)(2)] have been obtained from the aqueous ethanolic, aqueous and dioxan solutions, respectively. Oligomeric structures of polynuclear complexes are suggested to be via the bridging of copper atoms through electron donating atoms of bidentate thiouracil. The complex, [CU3(H,TU)4(HTU)(OH)2], reacts with concentrated HCl to give [Cu-3(H2TU)(4)Cl-3], in which its trinuclear structure is preserved. The properties and structure of [Cu-3(H2TU)(4)Cl-3] are different from those of [Cu(H,TU)2 Cl], which is synthesized from cuprous chloride. Spectral, thermal, magnetic studies and elemental analyses for the complexes have been carried out.
Keywords: METAL COMPLEXES; THIOURACIL; NICKEL(II); COBALT(II); URACIL; ZINC(II)